PUISI LE ROSSIGNOL KARYA PAUL VERLAINE : SIMBOLISME MELANKOLI DAN REPRESENTASI KEHILANGAN CINTA PERTAMA - Izha Siti Chodizah1; Myrna Laksman-Huntley (JURNAL ILMU BUDAYA, 2026)
The distinctiveness of style and expression in poetry is often reflected in literary movements such as symbolism, using symbols to bridge the real world and the world of ideas while emphasizing musicality in verse. Verlaine frequently explored themes of love in his works. His poem Le Rossignol portrays the experience of losing a first love and transforms it into a universal symbol of human suffering. This study examines the representation of lost first love through a qualitative textual approach, drawing on the theories of poetry to analyze structure as a unified whole and of sound to assess vocal and consonantal musicality. The findings reveal that loss is expressed through alliteration, assonance, rhyme, and metrical freedom, while natural symbols such as the bird, tree, and moon project the poet’s inner state. Thus, Le Rossignol demonstrates how Verlaine employs sound and symbolism to articulate first love as an existential reflection on melancholy.